Sustained dysfunction of antiviral CD8+ T lymphocytes after infection with hepatitis C virus. - Gruener, N; Lechner, F; Jung, M; Diepolder, H; Gerlach, T; Lauer, G; Walker, B; Sullivan, J; Phillips, R; Pape, G; Klenerman, P (2001)
Hepatitis C virus (HCV) sets up persistent infection in the majority of those exposed. It is likely that, as with other persistent viral infections, the efficacy of T-lymphocyte responses influences long-term outcome. However, little is known about the functional capacity of HCV-specific T-lymphocyte responses induced after acute infection. We investigated this by using major histocompatibility complex class I-peptide tetrameric complexes (tetramers), which allow direct detection of specific CD8+ T lymphocytes ex vivo, independently of function. Here we show that, early after infection, virus-specific CD8+ T lymphocytes detected with a panel of four such tetramers are abnormal in terms of their synthesis of antiviral cytokines and lytic activity. Furthermore, this phenotype is commonly maintained long term, since large sustained populations of HCV-specific CD8+ T lymphocytes were identified, which consistently had very poor antiviral cytokine responses as measured in vitro. Overall, HCV-specific CD8+ T lymphocytes show reduced synthesis of tumor necrosis factor alpha (TNF-alpha) and gamma interferon (IFN-gamma) after stimulation with either mitogens or peptides, compared to responses to Epstein-Barr virus and/or cytomegalovirus. This behavior of antiviral CD8+ T lymphocytes induced after HCV infection may contribute to viral persistence through failure to effectively suppress viral replication.